Optimalisasi Program Rukun Warga Responsif Gender untuk Mewujudkan Kelurahan Dr.Soetomo Ramah Perempuan dan Peduli Anak - Mailinda Farhani; Nihlatul Falasifah (Universitas 45 Surabaya, 2024)
KRPPA (Kelurahan Ramah Perempuan dan Peduli Anak) is an urban village initiative that combines women's protection and empowerment programs with child rights protection and fulfillment programs. The incorporation of gender and child perspectives into the management of governance at the urban village level, urban village development, and community development and empowerment must be carried out in a planned, comprehensive, and sustainable manner in the long term. The purpose of the KRPPA program optimization research is to strengthen community empowerment with a focus on gender and children's rights. The KRPPA program initiated by the ministry aims to support the developmental needs of children in Kelurahan Dr. Soetomo, tailored to their specific needs. Kelurahan Dr. Soetomo collaborates in the implementation of KRPPA, one of which is through the socialization of Gender Responsive RW. By involving various parties such as parents and local government, this program has succeeded in creating a safe and supportive environment for children's development. The KRPPA assessment has 10 indicator scores that must be met. This comprehensive approach has shown the extent to which Kelurahan Dr.Soetomo has achieved a women- and child-friendly village. The method applied in the community service program in Dr. Soetomo Village, Tegalsari District, Surabaya City is Community Based Research (CBR). The stages carried out include the initial stage and the mentoring stage with the community. Optimization to realize a Women-Friendly and Child-Caring Village maintains RW that have indicated gender responsive RW with a score of 10.